Does the outcome of fresh embryo transfer affect the outcome of subsequent thawed embryo transfers from sibling oocytes in patients that utilized all their embryos?. (20th October 2022) - Oron, Galia; Ronen, Maya; Hochberg, Alyssa; Wertheimer, Avital; Altman, Eran; Sapir, Onit; Ben-Haroush, Avi; Shufaro, Yoel
Abstract: The association between fresh embryo transfer (ET) outcome and the subsequent frozen-thawed (FET) cycles that follow is not clear, mainly because of incomplete embryo cohort utilization. The aim of this study was to determine if the outcome of a fresh ET affects the frozen cumulative clinical pregnancy (CP) and live birth (LB) rates resulting from the utilization of all surplus embryos from sibling oocytes. Outcome measures were the FET cumulative CP and LB rates. Multivariate logistic regression was performed for the frozen cumulative CP rate and adjusted for age, the number of oocytes, fresh ET outcome and other confounders. A total of 1313 cycles met the inclusion criteria. The FET cumulative CP and LB rates were not affected by the outcome of the fresh ET. The FET cumulative CP rate increased with the number of oocytes collected regardless of whether a pregnancy was achieved in the fresh cycle or not. In multivariate analysis, age (OR = 0.96, 95% CI 0.94–0.98), protocol (OR = 0.13, 95% CI 0.03–0.57) and the number of oocytes (OR = 1.05, 95% CI 1.02–1.07) were associated with the frozen cumulative CP rate. It is concluded that fresh ET does not impact the outcome of the vitrified-thawed embryos from the same oocyte cohort.